2021
DOI: 10.1177/2050157920986190
|View full text |Cite
|
Sign up to set email alerts
|

Reducing parent-adolescent conflicts about mobile phone use: The role of parenting styles

Abstract: This study seeks to understand the role of parenting styles in reconciling parent-adolescent conflict about adolescents’ mobile phone use, through an examination of the effects of adolescents’ mobile phone use intensity, parenting styles, and their interaction effects on the conflicts. Multi-stage cluster sampling was used to collect a representative sample of 751 middle school students in an eastern province of China. The results indicated a positive relationship between the intensity of adolescents’ mobile p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
1
1
0
Order By: Relevance
“…Furthermore, in this study, Kim et al (2019) also showed that time spent on a smartphone was positively related to suicide attempts, even after adjusting for conflicts with family members or friends and poor academic performance due to smartphone use [19]. Another study showed a similar pattern of a positive relationship between the intensity of adolescents' smartphone use and parent-adolescent conflicts about smartphone use among adolescents in China [20].…”
Section: Introductionsupporting
confidence: 65%
“…Furthermore, in this study, Kim et al (2019) also showed that time spent on a smartphone was positively related to suicide attempts, even after adjusting for conflicts with family members or friends and poor academic performance due to smartphone use [19]. Another study showed a similar pattern of a positive relationship between the intensity of adolescents' smartphone use and parent-adolescent conflicts about smartphone use among adolescents in China [20].…”
Section: Introductionsupporting
confidence: 65%
“…Researchers also have concluded that there is a link between parental abuse and child behavioral disorders. This relationship is significant and shows that the family and especially parents’ behavior during childhood plays a vital role in the occurrence of behavioral disorders in childhood and adulthood [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reverse salience is also related to the criteria of conflict. Parental concern about adolescent smartphone use is common, and approximately one-third of adolescents report daily conflicts with their parents over smartphone use [12][13][14]. From a developmental perspective, the potential for conflict is heightened during adolescence, as the drive for independence and autonomy is a defining feature of this period of life [15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, adolescents view smartphones as facilitating and enhancing their autonomy, allowing them to communicate with peers, use social media, and search the internet without direct parental supervision [16]. Yang and Zhang [14] reported that parental responsiveness (e.g., "I can depend on my parents to help me out if I have a problem") might help to moderate conflict regarding smartphone use. However, they also reported that this approach is less effective as the intensity of smartphone use increases, suggesting that conflict may be inevitable for adolescents displaying problematic smartphone use.…”
Section: Introductionmentioning
confidence: 99%